A comparison of bayesian filters for orientation estimation - Paz, Claudio; Pérez Paina, Gonzalo; Toloza, Hugo (Universidad Nacional de Río Negro, 2013)
This work presents an empirical study that compares the performance of Bayesian filters for orientation estimation using data provided by an Inertial Measurement Unit. A two-stages measurement update was implemented for different variants of Kalman and particles filters using quaternions as orientation representation method. Empirical results show that all tested algorithms converge to the correct orientation even if the initial orientation is unknown.
Keywords: Mobile robotics; Position estimation; Orientation estimation; Bayesian filtering